Design of a 40nm CMOS Internet-of-Things regulator with fast power on and off - Zhong, Si Yuan (Nanyang Technological University, 2020)
Low Dropout (LDO) regulator is an important building block for Internet of Things (IoT) and System-on-Chip (SoC). The applications like mobile phones, wearable devices, sensor network and so forth. Due to low power/energy requirement, it is often required to be off for most of time to save energy and on when needed. Thus, in this project, a fast power ON and power OFF LDO regulator is designed to meet the stated objective. In this work, several circuit design techniques have been applied to an IoT regulator to provide fast power ON and OFF functions. The simulation results of the regulator, which is realized in 40nm CMOS technology with 1.2V input voltage and 1V output voltage, has shown that the wake-up time of 94.8nS and power-off time of 116.2nS for a capacitive load of 100pF and a step load current of 10mA. Compared to the reported work as a benchmark, it is significantly faster. The proposed circuit techniques are useful for fast switching LDO regulator applications.